Improving the organ donor card system in Switzerland (Swiss Medical Weekly, 2013)
This paper analyses the current organ donor card system in Switzerland and identifies five problems that may be partially responsible for the country’s low deceased organ donation rates. There are two minor issues concerning the process of obtaining a donor card: the Swisstransplant website understates the prospective benefits of donation, and the ease with which donor cards can be obtained raises questions regarding whether any consent to donation provided is truly informed. Furthermore, there are two major practical problems that might affect those who carry an organ donor card: the lack of a central donor registry increases the likelihood that donors’ wishes will be “lost”, and there is a high probability that family members will veto organ donation. The fact that these two practical problems are not mentioned to potential donors by Swisstransplant constitutes the fifth problem. Donation rates would probably improve if more accurate information about the benefits of donation were provided to potential donors, a central donor registry were created, and families were not permitted to veto donation from those on the registry.